2013
DOI: 10.1371/journal.pone.0065103
|View full text |Cite
|
Sign up to set email alerts
|

Early Spatial Frequency Processing of Natural Images: An ERP Study

Abstract: The present study examined the role of spatial stimulus frequencies in the early visual processing of natural scenes. The content of initially degraded (low- or high-pass filtered) pictures was progressively revealed in a sequence of steps by adding high or low spatial frequencies. Event Related Potentials (ERPs) were used to track the early stages of visual processing. Picture degradation modulated the topography of the P1, with an occipital midline distribution for the most degraded pictures, which became pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 53 publications
1
31
0
Order By: Relevance
“…Moreover, a more positive frontal P2 amplitude was identified for the red target condition than for the gray target condition. As stated in the introduction, the P2 component reflects the processing of object identification (Viggiano and Kutas, 2000), with the occipital P2 component reflecting the processing of low-level features of stimuli (Martínez et al, 2001;Hansen et al, 2011;De Cesarei et al, 2013) and the frontal P2 component reflecting visual feature detection of threats. Deeper feature detection increases the frontal P2 amplitudes accordingly (Carretié et al, 2001;Correll et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, a more positive frontal P2 amplitude was identified for the red target condition than for the gray target condition. As stated in the introduction, the P2 component reflects the processing of object identification (Viggiano and Kutas, 2000), with the occipital P2 component reflecting the processing of low-level features of stimuli (Martínez et al, 2001;Hansen et al, 2011;De Cesarei et al, 2013) and the frontal P2 component reflecting visual feature detection of threats. Deeper feature detection increases the frontal P2 amplitudes accordingly (Carretié et al, 2001;Correll et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have indicated that the P2 component reflects the processing of object identification (Viggiano and Kutas, 2000), which emerges at two scalp regions (occipital or frontal areas). The occipital P2 component is suggested to reflect the processing of low-level features of stimuli (e.g., spectral power of visual input) (Martínez et al, 2001;Hansen et al, 2011;De Cesarei et al, 2013). In contrast, the frontal P2 components are suggested to reflect visual feature detection of threats.…”
Section: Introductionmentioning
confidence: 99%
“…As noted earlier, task differences may alter spatial frequency processing in the N170 to faces [ 44 ]. Previously, we did not find evidence for such task-related differences in the N1 to objects [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, concerning the categorization of objects in scenes, there has been no previous assessment as to whether differences in diagnostic color, spatial frequency amplitude, and SC between categories are necessary to observe this early ERP differentiation. Building on a previous study (De Cesarei et al, 2013) which observed that the average spectral power was linearly related to the absolute amplitude of the P2, a positive ERP peak in the same latency range as the early ERP differential, this study examined the extent to which the early ERP differential is associated with the correct categorization of objects in scenes when spectral differences in amplitude are ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that the presence of diagnostic colors (e.g., colors that are typically associated with a class of scenes, such as blue for the sea) can modulate early ERPs related to scene identification (Goffaux et al, 2005). Similarly, a vast amount of data (e.g., De Cesarei, Mastria, & Codispoti, 2013;Hansen, Jacques, Johnson, & Ellemberg, 2011;Joubert, Rousselet, Fabre-Thorpe, & Fize, 2009;Rousselet & Pernet, 2011;VanRullen, 2011) indicates that differences in image statistics may modulate early ERPs during scene or object categorization.…”
Section: Introductionmentioning
confidence: 99%